A 1.2nJ/Classification Fully Synthesized All-Digital Asynchronous Wired-Logic Processor Using Quantized Non-Linear Function Blocks in 0.18μm CMOS - Sumikawa, Rei; Shiba, Kota; Kosuge, Atsutake; Hamada, Mototsugu; Kuroda, Tadahiro (Proceedings of the 28th Asia and South Pacific Design Automation Conference, 2023)
A 5.3 times smaller and 2.6 times more energy-efficient all-digital wired-logic processor which infers MNIST with 90.6% accuracy and 1.2nJ of energy consumption has been developed. To improve area efficiency of wired-logic architecture, nonlinear neural network (NNN), which is a neuron and synapse efficient network, and logical compression technology to implement it with area-saving and low-power digital circuits by logic synthesis are proposed, and asynchronous digital combinational circuit DNN hardware has been developed.